Haemanthus snijmaniae (Amaryllidaceae), a new species from the arid regions in northwestern South Africa - Martínez-Azorín, Mario; Pinter, Michael; Crespo, Manuel B.; Alonso-Vargas, María Ángeles; Villar, José Luis; Human, Dawie J.; Kleeberger, Bernhard (Phytotaxa, 2025)
Field exploration in the arid regions of northwestern South Africa during March 2011 and August 2022 revealed an undescribed species of Haemanthus supported by distinct morphological characters, habitat, and biogeography. It agrees in morphology and distribution with an incompletely known taxon mentioned in the latest revision of the genus by D. Snijman, from some inselbergs in northern Bushmanland. Accordingly, Haemanthus snijmaniae, is here described as a new species. These plants show spreading to prostrate, plane, thin textured, immaculate, glabrous leaves; bracts thin textured and mostly not overlapping from base; short scape; few flowered inflorescences; short pedicels; and perigone tube only slightly widening upwards, not gibbose at tepal base. A complete morphological description of the new species is provided, as well as data on ecology, distribution, and differences with morphologically related species.